1994
DOI: 10.1084/jem.179.4.1233
|View full text |Cite
|
Sign up to set email alerts
|

Human CD4 restores normal T cell development and function in mice deficient in murine CD4.

Abstract: SummaryThe ability of a human coreceptor to function in mice was investigated by generating human CD4 (hCD4)-expressing transgenic mice on a mouse CD4-deficient (mCD4 -/-) background. From developing thymocyte to matured T lymphocyte functions, hCD4 was shown to be physiologically active. By examining the expansion and deletion of specific V/3 T cell families in mutated mice with and without hCD4, it was found that hCD4 can participate in positive and negative selection. Mature hCD4 single positive cells also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…We definitively show the expression of TCR␣ LCR-linked transgenes in cells of the B lineage. Because studies of hCD2 transgenes have shown its expression in the mouse B cell compartment (27,47), we were concerned that the ectopic B cell expression seen in our study may be an artifact of the hCD2 reporter. To address this concern, we examined the pattern of a TCR␣ LCR-linked human ␤-globin reporter fragment and still observed expression in B cells.…”
Section: Discussionmentioning
confidence: 99%
“…We definitively show the expression of TCR␣ LCR-linked transgenes in cells of the B lineage. Because studies of hCD2 transgenes have shown its expression in the mouse B cell compartment (27,47), we were concerned that the ectopic B cell expression seen in our study may be an artifact of the hCD2 reporter. To address this concern, we examined the pattern of a TCR␣ LCR-linked human ␤-globin reporter fragment and still observed expression in B cells.…”
Section: Discussionmentioning
confidence: 99%
“…These mutants have been previously described and exhibit normal trafficking to the cell surface as well as lck binding (16). Human CD4 molecules have been shown to be functional in mouse T cells in that they are able to rescue T cell development and function in CD4-deficient mice (19,20). These constructs were then used to infect CD4-deficient T cells, and sorted GFP-expressing cells were analyzed.…”
Section: Palmitoylation Sequences Of Cd4 Are Required For Tcr/pkc Clumentioning
confidence: 99%
“…The affinity of the human CD4 receptor for murine and human major histocompatibility complex class II (MHCII) is insufficient for activation of CD4/␥-expressing T cells. 1,2,[8][9][10][11] However, the consequences of such lowaffinity interactions on lymphoid development have not been examined.…”
Section: Introductionmentioning
confidence: 99%